Direct oxidation of hydrogen to hydrogen peroxide over Pd (or PdO)/Al2O3 in aqueous reaction medium: influence of different acids and halide anions in reaction medium on formation and destruction of H2O2 - Choudhary, Vasant R.; Ingole, Yugesh V.; Samanta, Chanchal; Jana, Prabhas (Industrial & Engineering Chemistry Research, 2007)
Effects of different mineral acids (viz. H2SO4, H3PO4, HNO3, HCl, HBr, and HI), acid (H3PO4) concentration, different halide anions (viz. F-, Cl-, Br-, and I-), and halide anion concentration in aqueous reaction medium on the H2O2 formation (in H-2-to-H2O2 oxidation) and/or on the H2O2 destruction (by H2O2 decomposition and hydrogenation) activities of Pd (or PdO)/Al2O3 catalyst (at 300 K and atmospheric pressure) have been thoroughly investigated. Among the different halide anions, Br- anions are most effective for promoting the H2O2 formation and inhibiting the H2O2 destruction by both the H2O2 decomposition and/or hydrogenation. The cations associated with the halide anions, however, have only a little or no influence on both the H2O2 formation and destruction. The concentration of the different halide anions has a strong influence on the H-2 conversion and H2O2 formation and destruction activities of the Pd/Al2O3. The H2O2 formation activity in the presence of Br- or Cl- anions is highest at the optimum concentration of halide (about 1.0 mmol/dm(3)). it is also highest at the optimum concentration of phosphoric acid (between 0.1 and 0.3 mol/dm(3)). In general, the H2O2 formation is increased with decreasing the H2O2 destruction activity of the catalyst, indicating a close relationship between the two. Br- anions act as an excellent catalyst promoter for Pd/Al2O3 catalyst, but they show only a small promoting effect for PdO/Al2O3 catalyst. The next choice for halide promoter for Pd/Al2O3 catalyst is Cl- anions. F- and I- anions are, however, catalyst inhibitor and strong poison, respectively, for the H2O2 formation. At the same concentration, Br- anions are more effective than Cl- anions for inhibiting the H2O2 destruction reactions over Pd/Al2O3 Catalyst. For both halide promoters (Cl- and Br-), the net H2O2 formation is controlled by the H2O2 hydrogenation rather than by the H2O2 decomposition.